Pengaruh Larutan Cuka Terhadap Struktur dan Kekerasan Tulang Ayam - Fata, Raihan Alimul; Prayogo, Muhammad Suwignyo; Febrian, Valentino Rahma; Anugraini, Putri Salsabilah; Nurohim, Ahmad (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to determine how vinega solution affects the structure and hardness of chicken thigh bones. Bones are composed of two main materials, namely calcium carbonate, which provides strength, and collagen, which makes them slightly flexible. When bones are immersed in a vinegar solution containing acetic acid, a chemical reaction called decalcification occurs, which is the dissolution of calcium carbonate from the bones. As a result, bones that were originally hard lose their mineral composition and become more flexible and easier to bend because only elastic collagen tissue remains. In the experiment, chicken bones were soaked in vinegar for five days, then changes in color, texture, and bone hardness were observed. The results showed that the bones became softer, paler in color, and less likely to break when bent. Through this experiment, it was understood how a simple chemical reaction can change the physical properties of hard objects such as bones, as well as providing insight into the importance of calcium in maintaining bone strength. This experiment also taught the close relationship between chemistry and biology in practical terms in everyday life.